Matriks Toeplitz dan Determinannya Menggunakan Metode Salihu - Miftahul Jannah; Yusmet Rizal (UNIVERSITAS NEGERI PADANG, 2023)
The matrix is a rectangular array of numbers. In this range the numbers are called the entries of the matrix. In matrix calculations generally focus on square-shaped matrices. There is a matrix called the Toeplitz matrix. The Toeplitz matrix has the same operations and calculations as a square matrix in general, one method for calculating the determinant is the Sarrus method. There is an alternative method to solve the determinant of the matrix, namely the Salihu determinant. The purpose of this research is to know the determinant properties related to the Toeplitz matrix and to know the determinant of the n×n Toeplitz matrix with n≥3 using the Salihu method. The result of this study is that the completion of the Toeplitz matrix determinant calculation will produce the same value as the determinant calculation using the cofactor expansion method.